Secondary battery and manufacturing method thereof

JP7643574B2Active Publication Date: 2025-03-11MURATA MFG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023549721
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-21
Filing Date
2022-09-21
Publication Date
2025-03-11
Estimated Expiration
2042-09-21

AI Technical Summary

Benefits of technology

【0013】 本発明の二次電池においては、導電性粒子がセパレータを通過したり、またはセパレータ内に滞留したりすることがなくなるため、電池の短絡やサイクル特性の低下を十分に防止できる。この時、セパレータの表層付近の異常大細孔を除いて考えることで、導電性粒子およびセパレータの設計自由度が広がる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643574000002
    Figure 0007643574000002
  • Figure 0007643574000003
    Figure 0007643574000003
  • Figure 0007643574000001
    Figure 0007643574000001
Patent Text Reader

Abstract

The present invention provides a secondary battery in which short-circuiting is more sufficiently prevented and which has sufficiently excellent rate characteristics and cycle characteristics. The present invention pertains to a secondary battery 10 that includes: a semi-solid electrode 1 (1a, 1b) that includes an electrode active material 2 (2a, 2b), an electroconductive aid 3 (3a, 3b), and an electrolytic solution 4 (4a, 4b); and, a separator 5 disposed in contact with the semi-solid electrode, the minimum particle diameter D5P (μm) of electroconductive particles included in the semi-solid electrode being greater than the maximum pore diameter D95 (μm) of an intermediate layer region of the separator.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery, in particular a secondary battery including a semi-solid electrode, and a method for producing the same. [Background technology]

[0002] Conventionally, secondary batteries have been used as power sources for various electronic devices. A secondary battery generally has a structure in which a laminate in which a positive electrode having a positive electrode layer and a negative electrode having a negative electrode layer are alternately laminated with a separator interposed therebetween, and an electrolyte is housed within an exterior body. In addition, as electrodes such as a positive electrode and a negative electrode, a binder-bonded electrode in which an electrode active material, a conductive assistant, and the like are bound by a binder on a current collector is used.

[0003] On the other hand, secondary batteries using semi-solid electrodes having fluidity instead of binder-bonded electrodes are known for the purposes of simplifying and reducing manufacturing costs, reducing inactive components in electrodes and secondary batteries, and improving energy density, charge capacity, and overall performance (e.g., Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2016-500465 Summary of the Invention [Problem to be solved by the invention]

[0005] The inventors of the present invention have found that the following new problems arise in conventional secondary batteries.

[0006] (1) In the binder-bonded electrode, the binder is present in a relatively large amount, which hinders the movement of electrons and ions and increases the electrical resistance, resulting in a decrease in rate characteristics.

[0007] (2) A method for producing a secondary battery including a binder-bonded electrode includes, as electrode production steps, a preparation step of preparing a coating liquid for forming an electrode layer; a coating step of coating a current collector with the coating liquid for forming an electrode layer; a drying step of drying the coated electrode layer; a pressing step of compacting the electrode precursor; a slitting step of cutting the electrode precursor to a desired width; and a cutting step of cutting the electrode precursor to a desired size to form an electrode plate; and, as assembly steps, a welding step of connecting a tab to the electrode plate; a housing step of stacking the electrode plates so that positive and negative electrode plates are arranged alternately with a separator arranged between them, and housing the laminate in an exterior body; a liquid injection step of injecting an electrolyte into the exterior body; a vacuum impregnation step of impregnating the electrodes with the electrolyte while maintaining a vacuum inside the exterior body; a vacuum sealing step of sealing the exterior body; a charge and discharge step of forming a solid electrolyte interface coating on the surface of the negative electrode active material by an initial charging treatment to form a secondary battery precursor; and an aging step of aging the secondary battery precursor. Such a complicated and lengthy manufacturing process increases the capital investment and manufacturing process costs, raising the manufacturing cost of the secondary battery.

[0008] (3) In secondary batteries containing semi-solid electrodes, when conductive particles pass through the pores of the separator and / or migrate and remain within the pores, the battery short-circuits during long-term use, and cycle characteristics deteriorate.

[0009] An object of the present invention is to provide a secondary battery which is more sufficiently prevented from short-circuiting and which has sufficiently excellent rate characteristics and cycle characteristics, and a method for producing the same.

[0010] Another object of the present invention is to provide a secondary battery which is more sufficiently prevented from short-circuiting, has sufficiently excellent rate characteristics and cycle characteristics, and can be produced in fewer production steps, and a production method thereof. [Means for solving the problem]

[0011] The present invention relates to A semi-solid electrode including an electrode active material, a conductive assistant, and an electrolyte, and a separator disposed in contact with the semi-solid electrode, The minimum particle size D5 of the conductive particles contained in the semi-solid electrode P (μm) is larger than the maximum pore diameter D95 (μm) of the intermediate layer region of the separator.

[0012] The present invention also provides The present invention relates to a method for producing the above-mentioned secondary battery, the method comprising the steps of: a preparation step of mixing an electrode active material, a conductive assistant, and an electrolyte to prepare a slurry for an electrode layer; a coating step of coating a current collector with a slurry for an electrode layer to form an electrode plate; A welding process for welding the tabs to the electrode plates; a housing step of stacking the electrode plates such that the positive and negative electrode plates are alternately arranged with separators disposed therebetween, and housing the stack in an exterior packaging material; A vacuum sealing process in which the exterior body material is sealed and a vacuum is created inside the exterior body; A charge-discharge process in which a solid electrolyte interfacial coating is formed on the surface of the negative electrode active material by an initial charging process to form a secondary battery precursor; and An aging step of aging the secondary battery precursor. Effect of the Invention

[0013] In the secondary battery of the present invention, the conductive particles do not pass through the separator or remain in the separator, so that short circuits and deterioration of cycle characteristics of the battery can be sufficiently prevented. At this time, the degree of freedom in designing the conductive particles and the separator is increased by excluding the abnormally large pores near the surface layer of the separator. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic example of a basic structure of a secondary battery according to one embodiment of the present invention, for illustrating the relationship between the minimum particle size D5P (μm) of conductive particles contained in a semi-solid electrode and the maximum pore size D95 (μm) of an intermediate layer region of a separator. [Diagram 2]FIG. 2 is a cross-sectional view showing a schematic diagram of an integrated active material and a conductive assistant, for illustrating the relationship between the active material and the conductive assistant that may be included in a secondary battery according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] [Secondary battery] The present invention provides a secondary battery. In this specification, the term "secondary battery" refers to a battery that can be repeatedly charged and discharged. The term "secondary battery" is not limited to its name, and may also include electrochemical devices such as "electricity storage devices". In this specification, "planar view" refers to a state (top view or bottom view) when an object is viewed from above or below (particularly from above) along the thickness direction (for example, the stacking direction of electrodes and separators). In this specification, "cross-sectional view" refers to a cross-sectional state (cross-sectional view) when viewed from a direction perpendicular to the thickness direction. It should be noted that the various elements shown in the drawings are merely shown diagrammatically for understanding the present invention, and that the dimensional ratio and appearance may differ from the actual objects. The "up-down direction", "left-right direction", and "front-back direction" used directly or indirectly in this specification correspond to the up-down direction, left-right direction, and front-back direction in the drawings, respectively. Unless otherwise specified, the same symbols or symbols indicate the same members or the same meanings. In a preferred embodiment, the vertical downward direction (i.e., the direction in which gravity acts) can be considered to correspond to the "downward direction", and the opposite direction can be considered to correspond to the "upward direction".

[0016] The secondary battery of the present invention will be described in detail below with reference to the drawings. In the present invention, each member constituting the secondary battery is arranged on the positive electrode side and the negative electrode side, respectively, unless otherwise specified, and the members and dimensions on the positive electrode side are represented by a symbol including "a", and the members and dimensions on the negative electrode side are represented by a symbol including "b". For example, the electrode 1 includes a positive electrode 1a and a negative electrode 1b. Also, for example, the electrode active material (or active material) 2 includes a positive electrode active material 2a and a negative electrode active material 2b. Also, for example, the conductive assistant 3 includes a positive electrode conductive assistant 3a and a negative electrode conductive assistant 3b. Also, for example, the electrolyte 4 includes a positive electrode electrolyte 4a and a negative electrode electrolyte 4b. Note that the positive electrode electrolyte 4a and the negative electrode electrolyte 4b may be electrolytes of the same composition.

[0017] As shown in FIG. 1, the secondary battery 10 of the present invention includes a semi-solid electrode 1 (1a, 1b) and a separator 5 arranged in contact with the semi-solid electrode. The semi-solid electrode 1 (1a, 1b) is usually an electrode that includes an electrode active material 2 (2a, 2b), a conductive assistant 3 (3a, 3b), and an electrolyte 4 (4a, 4b), and has an electrode layer having fluidity, and is also called a clay electrode. The conductive assistant 3 does not necessarily have to be included in both the semi-solid positive electrode 1a and the semi-solid negative electrode 1b, but may be included in one of these electrodes (particularly the positive electrode 1a). For example, both the positive electrode 1a and the negative electrode 1b may each include the conductive assistant 3 (3a, 3b). For example, the positive electrode 1a may include the conductive assistant 3a, and the negative electrode 1b may not include the conductive assistant 3b. For example, the positive electrode 1a may not include the conductive assistant 3a, and the negative electrode 1b may include the conductive assistant 3b. Typically, at least the positive electrode 1a contains the conductive assistant 3. Fig. 1 is a cross-sectional view showing a schematic example of the basic structure of a secondary battery according to an embodiment of the present invention.

[0018] In the present invention, both electrodes (i.e., positive and negative electrodes) 1a, 1b are usually semi-solid electrodes. Thus, the positive electrode 1a and the negative electrode 1b correspond to the semi-solid positive electrode 1a and the semi-solid negative electrode 1b, respectively. The term "semi-solid electrode" means that the electrode layer (particularly the material) is a mixture of a solid phase and a liquid phase, and the mixture may have the form of, for example, a slurry or a particle suspension. Thus, the electrode layer of the semi-solid electrode (i.e., the semi-solid electrode layer) is specifically composed of a slurry containing an electrode active material (usually solid-phase particles) and an electrolyte (usually liquid phase), and may further contain additives such as a conductive assistant (usually solid-phase particles). Unlike conventional binder-bound electrode layers, such semi-solid electrode layers do not contain a binder for binding and / or mutually fixing the electrode active materials. In the present invention, since the electrode (particularly the electrode layer) does not contain such a binder, an increase in electrical resistance caused by the binder can be avoided, and a further increase in the capacity of the secondary battery can be achieved. In the present invention, the semi-solid electrode (particularly the semi-solid electrode layer) does not strictly have to contain no binder. The present invention does not preclude the inclusion of a trace amount of binder as an impurity unintentionally mixed into the electrode layer during the manufacturing process, and an integration promoter (particularly a binder) described below for integrating the conductive assistant with the electrode active material surface. From this viewpoint, the content of the binder contained in the semi-solid electrode (particularly the semi-solid electrode layer) may be 0.1 mass % or less, particularly 0.01 mass % or less, based on the total amount of the semi-solid electrode layer. The content of the binder may be within the above range in each of the semi-solid positive electrode layer or the semi-solid negative electrode layer (particularly the semi-solid positive electrode layer). The binder is a binder that plays a role of connecting between electrode active materials, between the electrode active material / conductive assistant, and between the electrode active material / current collector in the electrode layer. The binder is usually a polymer having a weight average molecular weight of 1000 or more (for example, 5000 or more), particularly 10000 or more.

[0019] In the present invention, the semi-solid electrode and the separator disposed in direct contact with the semi-solid electrode have the following specific particle size-pore size relationship (hereinafter, sometimes simply referred to as "specific particle size-pore size relationship").

[0020] The "specific particle size-pore size relationship" refers to the minimum particle size D5 of the conductive particles contained in the semi-solid electrode (particularly the semi-solid electrode layer). P This refers to the relationship between the maximum pore size D95 (μm) of the separator placed in contact with the semi-solid electrode layer, and in detail, the minimum particle size D5 P The minimum particle diameter D5 (μm) of the conductive particles is larger than the maximum pore diameter D95 (μm) of the separator. Therefore, the conductive particles are more sufficiently prevented from passing through the separator or being retained in the separator, so that the secondary battery can be sufficiently prevented from short-circuiting or from deteriorating in cycle characteristics. P When the pore size D95 (μm) is equal to or smaller than the maximum pore size D95 (μm) of the separator, unless conductive particles (particularly conductive additives) are used integrated on the surface of the electrode active material, the conductive particles pass through the separator and / or remain within the separator, causing a short circuit in the secondary battery and deteriorating the cycle characteristics.

[0021] The conductive particles refer to a conductive assistant (e.g., including its primary particles, agglomerated particles, or a mixture thereof) contained in a semi-solid electrode (particularly in its semi-solid electrode layer), an integrated particle in which a conductive assistant is integrated on the surface of an electrode active material, or a mixture thereof. The conductive particles refer particularly to a conductive assistant (e.g., including its primary particles, agglomerated particles, or a mixture thereof) contained in a semi-solid electrode (particularly in its semi-solid electrode layer), or an integrated particle in which a conductive assistant is integrated on the surface of an electrode active material. The conductive particles do not usually include a single electrode active material.

[0022] Minimum conductive particle size D5 P (μm) refers to the minimum particle size D5 value of the conductive particles. D5 is the particle size when the cumulative particle volume from the small particle size side reaches 5% of the total particle volume in the particle size distribution obtained by the laser diffraction / scattering method. Therefore, D5 (μm) refers to the above-mentioned specified particle size when the cumulative frequency of the conductive particles from the minimum particle size to the specified particle size is 5%. Therefore, D5 is a particle size relatively close to the minimum particle size.

[0023] Minimum conductive particle size D5 P The minimum particle diameter D5 (μm) of the conductive particles can be measured by determining the particle size distribution by a laser diffraction / scattering method using a semi-solid electrode layer taken out of a secondary battery as a sample. The particle size distribution measuring device is not particularly limited as long as it is a measuring device using the laser diffraction / scattering method, and for example, a commercially available LA-960 (manufactured by Horiba, Ltd.) can be used. Note that the measured particle size distribution usually shows a part of the particle size distribution of each material such as the conductive assistant and the electrode active material overlapping, but by breaking it down into the particle size distribution of each material and identifying the materials that make up each particle size distribution, the minimum particle diameter D5 P In addition, if the particle size distribution overlaps significantly and it is difficult to separate the particle size distribution, the electrode can be diluted with an organic solvent such as NMP, and the particles can be separated into each material using the difference in specific gravity, after which the particle size distribution can be measured.

[0024] Minimum conductive particle size D5 P The minimum particle size D5 (μm) of the conductive additive can be controlled by adjusting the D5 of the conductive additive used. For example, by using a conductive additive with a larger D5, the minimum particle size D5 of the conductive particles can be controlled by adjusting the D5 of the conductive additive. P For example, by using a conductive assistant with a smaller D5, the minimum particle size D5 of the conductive particles can be increased. P In particular, when the conductive assistant is integrated with the surface of the electrode active material as described below, the minimum particle diameter D5 of the conductive particles can be reduced by using an electrode active material with a larger D5. P In this case, the minimum particle size D5 of the conductive particles can be increased by using an electrode active material with a smaller D5. P The D5 of the conductive assistant and the electrode active material can be controlled by classification. For example, the minimum particle size D5 of the conductive particles can be reduced by removing small particles from the conductive assistant by classification. P In addition, for example, by removing large particles from the conductive additive by classification, the minimum particle size D5 P (μm) can be made smaller.

[0025] The maximum pore diameter D95 (μm) of the separator refers to the maximum pore diameter D95 (μm) of the intermediate layer region in the separator. The intermediate layer region refers to a region 52 excluding the surface layer 51 on the front and back surfaces of the separator 5 in a cross section parallel to the thickness direction of the separator 5 as shown in FIG. 1. More specifically, the intermediate layer region refers to a region 52 excluding a region 51 that is 15% of the thickness of the separator at each end in the thickness direction in a cross section parallel to the thickness direction of the separator 5 as shown in FIG. 1. In this way, by considering the maximum pore diameter of the separator excluding the abnormally large pores in the surface layer 51 of the separator 5, the design freedom of the conductive particles and the separator is expanded. Note that the "region 51 that is 15% of the thickness of the separator" refers to the "region 51 that is 15% of the thickness of the separator in the completed secondary battery".

[0026] The maximum pore diameter D95 (μm) of such an intermediate layer region 52 in the separator is the pore diameter when the cumulative pore volume from the small diameter side reaches 95% of the total pore volume in the pore diameter distribution obtained by image analysis (e.g., image analysis using the software "ImageJ") based on a cross-sectional image obtained by SEM observation. Therefore, D95 (μm) refers to the above-mentioned specified pore diameter when the cumulative frequency obtained by accumulating the frequencies of the pore diameters of the separator from the smallest diameter to the specified pore diameter is 95%. Therefore, D95 is a pore diameter relatively close to the maximum pore diameter.

[0027] The maximum pore diameter D95 (μm) of the separator can be measured by using a separator taken out of a secondary battery as a sample, exposing the cross section of the separator by FIB processing (Focused Ion Beam) while cooling, and determining the pore size distribution by image analysis of the cross section image (particularly the intermediate layer region) based on SEM observation. The measuring device for the pore size distribution is not particularly limited, and for example, a commercially available ImageJ (Wayne Rasband (NIH)) can be used. The measurement range of the pore size distribution is preferably the thickness of the intermediate layer region excluding the upper and lower 15% regions and a width of 100 μm or more in the direction perpendicular to the thickness direction.

[0028] Minimum conductive particle size D5 P From the viewpoint of more sufficiently preventing short circuits and further improving rate characteristics and cycle characteristics, it is desirable for the R2 (μm) and the maximum pore diameter D95 (μm) of the separator to satisfy the following relationship: Preferably, 0.1≦D5 P -D95≦10; More preferably, 0.2≦D5 P -D95≦9; More preferably, 1≦D5 P -D95≦9; Particularly preferably, 5≦D5 P -D95≦8.

[0029] Minimum conductive particle size D5 P is not particularly limited and may be, for example, 0.3 μm or more and 15 μm or less, and from the viewpoint of more sufficiently preventing short circuits and further improving rate characteristics and cycle characteristics, it is preferably 0.5 μm or more and 12 μm or less, more preferably 1 μm or more and 10 μm or less, even more preferably 3 μm or more and 10 μm or less, and particularly preferably 5 μm or more and 10 μm or less.

[0030] The maximum pore size D95 of the separator is not particularly limited and may be, for example, 0.2 μm or more and 5 μm or less. From the viewpoint of more sufficiently preventing short circuits and further improving rate characteristics and cycle characteristics, it is preferably 0.2 μm or more and 4 μm or less, more preferably 0.2 μm or more and 3 μm or less, even more preferably 0.5 μm or more and 3 μm or less, and particularly preferably 0.5 μm or more and 2 μm or less.

[0031] The semi-solid electrode having the above-mentioned "specific particle size-pore size relationship" and the separator arranged in contact with the semi-solid electrode correspond to the semi-solid electrode layer having the above-mentioned "specific particle size-pore size relationship" and the separator arranged in contact with the semi-solid electrode layer, respectively.

[0032] A semi-solid electrode typically comprises a current collector having a semi-solid electrode layer on at least one side of the current collector. For example, when a semi-solid electrode has a current collector and a semi-solid electrode layer disposed on only one side of the current collector, the "specific particle size-pore size relationship" may be achieved between the semi-solid electrode layer and a separator disposed in contact with the semi-solid electrode layer. Also, for example, when a semi-solid electrode has a current collector and semi-solid electrode layers disposed on both sides of the current collector, the "specific particle size-pore size relationship" may be achieved between at least one of the semi-solid electrode layers and a separator disposed in contact with the semi-solid electrode layer. In this case, from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, the "specific particle size-pore size relationship" is preferably achieved between one of the semi-solid electrode layers and a separator disposed in contact with the semi-solid electrode layer, and between the other semi-solid electrode layer and a separator disposed in contact with the semi-solid electrode layer.

[0033] The above-mentioned "specific particle size-pore size relationship" may be achieved between at least one of the electrodes (particularly the electrode layer) of the semi-solid positive electrode or the semi-solid negative electrode and the separator arranged in contact with the electrode (particularly the electrode layer). In the present invention, the conductive assistant may be contained in at least one of the semi-solid positive electrode (particularly the electrode layer) or the semi-solid negative electrode (particularly the electrode layer). The average particle size of the conductive assistant is usually much smaller than the average particle size of the electrode active material. In particular, the D5 of the conductive assistant is usually much smaller than the D5 of the electrode active material. Thus, the present invention encompasses the following embodiments depending on the component compositions of the semi-solid positive electrode and the semi-solid negative electrode:

[0034] EMBODIMENT 1 When the conductive assistant is contained in both the positive and negative electrodes, the specific particle size-pore size relationship is achieved in any one of the following forms (A) to (C). From the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, the specific particle size-pore size relationship is preferably achieved in form (A) or (B), and more preferably achieved in form (A): Form (A): between a positive electrode and a separator disposed in contact with the positive electrode, and between a negative electrode and a separator disposed in contact with the negative electrode; Form (B): between a positive electrode and a separator disposed in contact with the positive electrode; (in this case, the specific particle size-pore size relationship does not have to be achieved between a negative electrode and a separator disposed in contact with the negative electrode); Form (C): Between a negative electrode and a separator arranged in contact with the negative electrode; (In this case, the specific particle size-pore size relationship does not have to be achieved between a positive electrode and a separator arranged in contact with the positive electrode).

[0035] EMBODIMENT 2 When a conductive assistant is contained in the positive electrode but not in the negative electrode, it is preferable that the specific particle size-pore size relationship is achieved in the above form (B) from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics.

[0036] EMBODIMENT 3 When a conductive assistant is contained in the negative electrode but not in the positive electrode, it is preferable that the specific particle size-pore size relationship is achieved in the above form (C) from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics.

[0037] In the present invention, from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, embodiments 1 and 2 are preferred, and embodiment 1 is more preferred.

[0038] The positive electrode active material 2a contained in the positive electrode 1a and the negative electrode active material 2b contained in the negative electrode 1b are materials directly involved in the transfer of electrons in the secondary battery, and are the main materials of the positive and negative electrodes that are responsible for charging and discharging, i.e., the battery reaction. More specifically, ions are brought to the electrolyte due to the "positive electrode active material contained in the positive electrode" and the "negative electrode active material contained in the negative electrode", and these ions move between the positive electrode and the negative electrode to transfer electrons and charge and discharge. Such mediator ions are not particularly limited as long as they can be charged and discharged, and examples thereof include lithium ions or sodium ions (particularly lithium ions). The positive electrode and the negative electrode may be electrodes that can particularly absorb and release lithium ions. In other words, the secondary battery of the present invention may be a secondary battery in which lithium ions move between the positive electrode active material and the negative electrode active material via the electrolyte to charge and discharge the battery. When lithium ions are involved in charging and discharging, the secondary battery of the present invention corresponds to a so-called "lithium ion battery".

[0039] The positive electrode active material 2a of the positive electrode 1a is preferably made of, for example, granular material. Furthermore, it is also preferable that a conductive assistant is contained in the positive electrode (particularly the positive electrode layer) in order to facilitate the transfer of electrons that promote the battery reaction. Similarly, the negative electrode active material 2b of the negative electrode 1b is preferably made of, for example, granular material, and a conductive assistant may be contained in the negative electrode (particularly the negative electrode layer) in order to facilitate the transfer of electrons that promote the battery reaction. In this way, since a plurality of components are contained, the positive electrode layer and the negative electrode layer can also be called "positive electrode composite layer" and "negative electrode composite layer", respectively.

[0040] The positive electrode active material 2a may be a material that contributes to the absorption and release of lithium ions. From this perspective, the positive electrode active material may be, for example, a lithium-containing composite oxide. More specifically, the positive electrode active material may be a lithium transition metal composite oxide containing lithium and at least one transition metal selected from the group consisting of cobalt, nickel, manganese, and iron. In other words, in the positive electrode layer of the secondary battery according to the present invention, such a lithium transition metal composite oxide may be preferably contained as the positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium iron phosphate, or a material in which a part of the transition metal is replaced with another metal. Such a positive electrode active material may be contained as a single type, or may be contained in a combination of two or more types. In a more preferred embodiment, the positive electrode active material contained in the positive electrode (particularly the positive electrode layer) is lithium cobalt oxide.

[0041] The average particle size of the positive electrode active material is not particularly limited and may be, for example, 1 μm or more and 100 μm or less, particularly 1 μm or more and 50 μm or less. From the viewpoint of more sufficiently preventing short circuits and further improving rate characteristics and cycle characteristics, the average particle size is preferably 1 μm or more and 30 μm or less, and more preferably 10 μm or more and 20 μm or less.

[0042] The average particle size of the positive electrode active material is the particle size D50 when the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution obtained by the laser diffraction / scattering method. The particle size distribution for measuring the average particle size of the positive electrode active material is the minimum particle size D5 P The particle size distribution can be measured by using a measuring device similar to that used for measuring the particle size distribution.

[0043] Minimum particle size D5 of positive electrode active material M It may usually be 0.5 μm or more and 50 μm or less, particularly 1 μm or more and 40 μm or less, and from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, it is preferably 2 μm or more and 20 μm or less, more preferably 4 μm or more and 15 μm or less.

[0044] Minimum particle size D5 of positive electrode active material M (μm) refers to the minimum particle size D5 value of the positive electrode active material. The D5 is the minimum particle size D5 of the conductive particles. P Similarly, this is the particle size at which the cumulative particle volume from the small particle size side reaches 5% of the total particle volume in the particle size distribution determined by laser diffraction / scattering method.

[0045] Minimum particle size D5 of positive electrode active material M (μm) is the minimum particle size D5 of the conductive particles, except that the positive electrode active material is used as the sample. P It can be measured by the same method as above.

[0046] The content of the positive electrode active material is usually 50% by weight or more and 90% by weight or less, based on the total amount of the positive electrode layer, and from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, it is preferably 70% by weight or more and 90% by weight or less.

[0047] The conductive assistant that may be included in the positive electrode 1a is not particularly limited, but may be at least one selected from carbon black such as thermal black, furnace black, channel black, ketjen black, and acetylene black, carbon fibers such as graphite, carbon nanotubes, and vapor-grown carbon fibers, metal powders such as copper, nickel, aluminum, and silver, and polyphenylene derivatives. In a more preferred embodiment, the conductive assistant of the positive electrode layer is carbon black. In a further preferred embodiment, the positive electrode active material and conductive assistant of the positive electrode layer are a combination of lithium cobalt oxide and carbon black.

[0048] The average particle size of the conductive assistant contained in the positive electrode (particularly the positive electrode layer) is not particularly limited and may be, for example, 0.1 μm or more and 20 μm or less, particularly 0.1 μm or more and 10 μm or less. From the viewpoint of more sufficiently preventing short circuits and further improving the rate characteristics and cycle characteristics, it is preferably 0.5 μm or more and 8 μm or less, more preferably 1 μm or more and 5 μm or less.

[0049] The average particle size of the conductive assistant contained in the positive electrode (particularly the positive electrode layer) is the particle size D50 at which the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution obtained by the laser diffraction / scattering method. The particle size distribution for measuring the average particle size of the conductive assistant is the minimum particle size D5 P The particle size distribution can be measured by using a measuring device similar to that used for measuring the particle size distribution.

[0050] Minimum particle size D5 of the conductive additive contained in the positive electrode (especially the positive electrode layer) A may usually be 0.01 μm or more and 10 μm or less, particularly 0.05 μm or more and 5 μm or less, and from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, it is preferably 0.1 μm or more and 4 μm or less, more preferably 0.1 μm or more and 2 μm or less, and particularly preferably 0.1 μm or more and 0.5 μm or less.

[0051] Minimum particle size D5 of the conductive additive contained in the positive electrode (especially the positive electrode layer) A (μm) refers to the minimum particle size D5 value of the conductive additive. The D5 is the minimum particle size D5 of the conductive particles. P Similarly, this is the particle size at which the cumulative particle volume from the small particle size side reaches 5% of the total particle volume in the particle size distribution determined by laser diffraction / scattering method.

[0052] Minimum particle size D5 of the conductive additive contained in the positive electrode (especially the positive electrode layer) A (μm) is the minimum particle size D5 of the conductive particles, except for the conductive assistant contained in the positive electrode (especially the positive electrode layer) as a sample. P It can be measured by the same method as above.

[0053] The content of the conductive assistant contained in the positive electrode (particularly the positive electrode layer) is usually 0.1% by weight or more and 10% by weight or less, based on the total amount of the positive electrode layer, and from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, it is preferably 0.5% by weight or more and 5% by weight or less, and more preferably 1% by weight or more and 3% by weight or less.

[0054] The conductive assistant contained in the positive electrode (particularly the positive electrode layer) has a minimum particle size D5 that is equal to or smaller than the maximum pore size D95 (μm) of the separator that is placed in contact with the positive electrode layer. A When the conductive assistant has a diameter of 1 μm or less, it is preferable that the conductive assistant 3 (3a) is integrated with the surface of the electrode active material 2 (positive electrode active material 2a) as shown in FIG. 2. By using the conductive assistant by adhering and integrating it with the surface of the electrode active material (positive electrode active material), the minimum particle diameter D5 A This is because the above-mentioned "specific particle size-pore size relationship" can be satisfied even if a conductive assistant having a minimum particle size D5 (μm) is used. A Since a conductive assistant having a smaller diameter (μm) can be used, the surface area of ​​the conductive assistant used can be increased even with the same weight. As a result, electronic conductivity in the electrode can be improved and electronic resistance can be reduced. Fig. 2 is a cross-sectional view showing a schematic diagram of an integrated active material and a conductive assistant to show the relationship between the active material and the conductive assistant that may be included in the secondary battery of the present invention.

[0055] The integrated particles in which the conductive assistant 3 is integrated (and / or fixed) on the surface of the electrode active material 2 can be obtained by subjecting a mixture of the electrode active material 2 and the conductive assistant 3 to a mechanochemical treatment. The mechanochemical treatment is a treatment in which mechanical energy (e.g., shear force, impact force, grinding force, etc.) is applied to the mixture of the electrode active material 2 and the conductive assistant 3 to form a physical and / or chemical bond between the electrode active material and the conductive assistant. The mechanochemical treatment may be, for example, a mixing treatment, a grinding treatment, or a stirring treatment.

[0056] The mechanochemical treatment can be carried out using any device capable of transmitting mechanical energy (e.g., a so-called mixing device, grinding device, or stirring device). For example, the treatment can be carried out using a device such as Nobilta manufactured by Hosokawa Micron Corporation.

[0057] The mixture to be mechanochemically treated may further contain an integration promoter. The integration promoter is a substance that promotes integration of the electrode active material and the conductive assistant, and for example, a binder contained in a conventional binder-bound electrode layer is used. Specific examples of the integration promoter include polymer compounds such as polyacrylonitrile, polyvinylidene fluoride, copolymers of vinylidene fluoride and hexafluoropropylene, polytetrafluoroethylene, polyhexafluoropropylene, polyethylene oxide, polypropylene oxide, polyphosphazene, polysiloxane, polyvinyl acetate, polyvinyl alcohol, polymethyl methacrylate, polyacrylic acid, polymethacrylic acid, styrene-butadiene rubber, nitrile-butadiene rubber, polystyrene and / or polycarbonate. From the viewpoint of more adequately preventing short circuits and further improving rate characteristics and cycle characteristics, it is preferable to use a polymer compound that is difficult to dissolve in the solvent of the electrolyte as the integration promoter. Examples of such integration promoters include polyvinylidene fluoride.

[0058] The content of the integration promoter is an amount such that the integration of the electrode active material and the conductive assistant is promoted while the content of the binder relative to the total amount of the semi-solid electrode layer is within the above-mentioned range, and may be, for example, 0.05 parts by mass or more and 0.13 parts by mass or less relative to 100 parts by mass of the electrode active material.

[0059] The conditions for the mechanochemical treatment, such as treatment time, treatment temperature, stirring speed, etc., are not particularly limited as long as the conductive assistant is integrated and fixed on the surface of the electrode active material.

[0060] The negative electrode active material 2b may be a material that contributes to the absorption and release of lithium ions. From this perspective, the negative electrode active material may be, for example, various carbon materials, oxides, or lithium alloys. Examples of various carbon materials for the negative electrode active material include graphite (natural graphite, artificial graphite), hard carbon, soft carbon, and diamond-like carbon. In particular, graphite is preferable because of its high electronic conductivity. Examples of oxides for the negative electrode active material include at least one selected from the group consisting of silicon oxide, tin oxide, indium oxide, zinc oxide, and lithium oxide. The lithium alloy for the negative electrode active material may be any metal that can form an alloy with lithium, and may be, for example, a binary, ternary, or more alloy of lithium and a metal such as Al, Si, Pb, Sn, In, Bi, Ag, Ba, Ca, Hg, Pd, Pt, Te, Zn, or La. It is preferable that such oxides have an amorphous structure. This is because deterioration caused by non-uniformity such as grain boundaries or defects is less likely to occur. In a more preferred embodiment, the negative electrode active material of the negative electrode is artificial graphite.

[0061] The average particle size of the negative electrode active material is not particularly limited and may be, for example, 0.5 μm or more and 50 μm or less, particularly 1 μm or more and 40 μm or less. From the viewpoint of more sufficiently preventing short circuits and further improving rate characteristics and cycle characteristics, it is preferably 2 μm or more and 30 μm or less, more preferably 5 μm or more and 20 μm or less.

[0062] The average particle size of the negative electrode active material is the particle size D50 when the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution obtained by the laser diffraction / scattering method. The particle size distribution for measuring the average particle size of the negative electrode active material is the minimum particle size D5 P The particle size distribution can be measured by using a measuring device similar to that used for measuring the particle size distribution.

[0063] Minimum particle size D5 of negative electrode active material MIt may usually be 0.5 μm or more and 50 μm or less, particularly 1 μm or more and 40 μm or less, and from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, it is preferably 2 μm or more and 20 μm or less, more preferably 2 μm or more and 10 μm or less.

[0064] Minimum particle size D5 of negative electrode active material M (μm) refers to the minimum particle size D5 value of the negative electrode active material. The D5 is the minimum particle size D5 of the conductive particles. P Similarly, this is the particle size at which the cumulative particle volume from the small particle size side reaches 5% of the total particle volume in the particle size distribution determined by laser diffraction / scattering method.

[0065] Minimum particle size D5 of negative electrode active material M (μm) is the minimum particle size D5 of the conductive particles, except that the negative electrode active material is used as the sample. P It can be measured by the same method as above.

[0066] The content of the negative electrode active material is usually 50% by weight or more and 70% by weight or less, based on the total amount of the negative electrode layer, and from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, it is preferably 55% by weight or more and 65% by weight or less.

[0067] The conductive assistant that may be contained in the negative electrode 1b is not particularly limited, but may be at least one selected from carbon blacks such as thermal black, furnace black, channel black, ketjen black, and acetylene black; carbon fibers such as carbon nanotubes and vapor-grown carbon fibers; metal powders such as copper, nickel, aluminum, and silver; and polyphenylene derivatives.

[0068] The average particle size of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) is not particularly limited and may be, for example, 0.1 μm or more and 20 μm or less, particularly 0.1 μm or more and 10 μm or less. From the viewpoint of more sufficiently preventing short circuits and further improving rate characteristics and cycle characteristics, it is preferably 0.5 μm or more and 8 μm or less, more preferably 1 μm or more and 5 μm or less.

[0069] The average particle size of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) is the particle size D50 at which the cumulative particle volume from the small particle size side reaches 50% of the total particle volume in the particle size distribution obtained by the laser diffraction / scattering method. The particle size distribution for measuring the average particle size of the conductive assistant is the minimum particle size D5 P The particle size distribution can be measured by using a measuring device similar to that used for measuring the particle size distribution.

[0070] Minimum particle size D5 of the conductive additive contained in the negative electrode (especially the negative electrode layer) A may usually be 0.01 μm or more and 10 μm or less, particularly 0.05 μm or more and 5 μm or less, and from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics, it is preferably 0.1 μm or more and 4 μm or less, more preferably 0.1 μm or more and 2 μm or less, and particularly preferably 0.1 μm or more and 0.5 μm or less.

[0071] Minimum particle size D5 of the conductive additive contained in the negative electrode (especially the negative electrode layer) A (μm) refers to the minimum particle size D5 value of the conductive additive. The D5 is the minimum particle size D5 of the conductive particles. P This is the same as the particle size at which the cumulative particle volume from the small particle size side reaches 5% of the total particle volume in the particle size distribution determined by laser diffraction / scattering method.

[0072] Minimum particle size D5 of the conductive additive contained in the negative electrode (especially the negative electrode layer) A (μm) is the minimum particle size D5 of the conductive particles, except for the conductive assistant contained in the negative electrode (especially the negative electrode layer) as a sample. P It can be measured by the same method as above.

[0073] The content of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) is usually 0% by weight or more and 10% by weight or less with respect to the total amount of the negative electrode layer, and from the viewpoint of more sufficient prevention of short circuit and further improvement of rate characteristics and cycle characteristics, it is preferably 0% by weight or more and 2% by weight or less, more preferably 0% by weight. The content of the conductive assistant contained in the negative electrode (particularly the negative electrode layer) being 0% by weight means that the negative electrode (particularly the negative electrode layer) does not contain the conductive assistant.

[0074] The conductive assistant contained in the negative electrode (particularly the negative electrode layer) has a minimum particle size D5 that is equal to or smaller than the maximum pore size D95 (μm) of the separator that is placed in contact with the negative electrode layer. A When the conductive assistant has a particle diameter of 0.1 μm or less, it is preferable that the conductive assistant 3 is integrated with the surface of the electrode active material 2 (negative active material) in the same manner as in the positive electrode (particularly the positive electrode layer). By using the conductive assistant by adhering and integrating it with the surface of the electrode active material, the minimum particle diameter D5 A This is because the above-mentioned "specific particle size-pore size relationship" can be satisfied even if a conductive assistant having a minimum particle size D5 (μm) is used. A Since a conductive additive with a smaller diameter (μm) can be used, the surface area of ​​the conductive additive used can be increased even with the same weight used. As a result, electronic conductivity in the electrode can be improved and electronic resistance can be reduced.

[0075] The electrolyte contained in the positive electrode 1a and the electrolyte contained in the negative electrode 1b usually have the same composition.

[0076] The electrolyte aids the movement of metal ions released from the electrode active materials (positive and negative active materials). The electrolyte may be a "non-aqueous" electrolyte such as an organic electrolyte or an organic solvent, or an "aqueous" electrolyte containing water. The secondary battery of the present invention is preferably a non-aqueous electrolyte secondary battery using an electrolyte containing a "non-aqueous" solvent and a solute as the electrolyte. The electrolyte may be in the form of a liquid or gel (note that in this specification, a "liquid" non-aqueous electrolyte is also referred to as a "nonaqueous electrolyte").

[0077] A specific solvent for the non-aqueous electrolyte is not particularly limited, and may be one that contains at least a carbonate. Such carbonate may be a cyclic carbonate and / or a chain carbonate. Although not particularly limited, the cyclic carbonate may be at least one selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC) and vinylene carbonate (VC). The chain carbonate may be at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dipropyl carbonate (DPC). In one preferred embodiment, a combination of a cyclic carbonate and a chain carbonate is used as the non-aqueous electrolyte, for example, a mixture of ethylene carbonate and ethyl methyl carbonate is used.

[0078] A specific example of the solute of the non-aqueous electrolyte is LiPF 6 and LiBF 4 In a preferred embodiment, Li salts such as LiPF 6 The concentration of the solute in the electrolyte is not particularly limited, and may be, for example, from 0.1 M to 10 M, particularly from 0.5 M to 3 M. M stands for moles / L.

[0079] The content of the electrolyte in the positive electrode (particularly the positive electrode layer) and the negative electrode (particularly the negative electrode layer) is not particularly limited. For example, the content of the electrolyte contained in the positive electrode (particularly the positive electrode layer) is usually 5% by weight or more and 50% by weight or less, and particularly 10% by weight or more and 30% by weight or less, based on the total amount of the positive electrode layer. Also, for example, the content of the electrolyte contained in the negative electrode (particularly the negative electrode layer) is usually 10% by weight or more and 70% by weight or less, and particularly 30% by weight or more and 50% by weight or less, based on the total amount of the negative electrode layer.

[0080] The thickness of the electrode layer is not particularly limited and may be appropriately selected according to the desired battery capacity. The thickness of the electrode layer (particularly the thickness of the electrode layer per one main surface (one side) of the current collector described later) is, for example, such that the capacity per electrode area in the secondary battery of the present invention falls within the range described later, and may usually be 100 μm or more, particularly 150 μm or more and 600 μm or less. The thickness of the electrode layer includes the thickness of the positive electrode layer and the thickness of the negative electrode layer, and each may be selected independently. The thickness of the electrode layer is the average value of the thicknesses at any 50 points in the completed secondary battery.

[0081] In FIG. 1, the current collector is omitted, but the electrode 1 (1a, 1b) usually includes a current collector. The electrode (particularly, a semi-solid electrode) 1 usually has an electrode layer (particularly, a semi-solid electrode layer) on at least one side (preferably both sides) of the current collector. The constituent material of the current collector is not particularly limited as long as it has electrical conductivity, and may be, for example, one metal selected from the group consisting of copper, aluminum, stainless steel, etc., or an alloy containing two or more metals. The current collector of the positive electrode is preferably made of aluminum from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics. The current collector of the negative electrode is preferably made of copper from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics.

[0082] There are no particular limitations on the thickness of the positive electrode and negative electrode current collectors, and they may each independently be, for example, from 1 μm to 300 μm, particularly from 1 μm to 100 μm.

[0083] The separator 5 is a member provided from the viewpoint of retaining the electrolyte while preventing short circuit caused by contact between the positive electrode active material 2a in the positive electrode 1a and the negative electrode active material 2b in the negative electrode 1b. In other words, the separator is a member that allows ions to pass while preventing electronic contact between the positive electrode layer and the negative electrode layer. The separator 5 is not particularly limited as long as it has such a function and has the above-mentioned maximum pore diameter D95 in the intermediate layer region. The separator is usually a porous or microporous insulating member, and has a membrane form due to its small thickness. Although it is merely an example, a microporous membrane made of polyolefin may be used as the separator. In this regard, the microporous membrane used as the separator may contain, for example, only polyethylene (PE) or only polypropylene (PP) as the polyolefin. Furthermore, the separator may be a laminate composed of a "PE microporous membrane" and a "PP microporous membrane". The surface of the separator may be covered with an inorganic particle coating layer.

[0084] The thickness of the separator 5 is not particularly limited as long as it has the above-mentioned maximum pore diameter D95 in the intermediate layer region, and may be, for example, 5 μm or more and 30 μm or less, and is preferably 15 μm or more and 25 μm or less from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics. The thickness of the separator 5 is the thickness in the completed secondary battery.

[0085] The secondary battery of the present invention is usually enclosed in an exterior body. The exterior body may be a flexible pouch (soft bag) or a hard case (hard housing). From the viewpoint of more sufficient prevention of short circuit and further improvement of rate characteristics and cycle characteristics, the exterior body is preferably a flexible pouch.

[0086] When the exterior body is a flexible pouch, the flexible pouch is usually formed from a laminate film, and the seal part is formed by heat-sealing the periphery. The laminate film is generally a film in which a metal foil and a polymer film are laminated, and specifically, a three-layer structure consisting of an outer layer polymer film / metal foil / inner layer polymer film is exemplified. The outer layer polymer film is for preventing damage to the metal foil due to permeation of moisture and the like and contact, and polymers such as polyamide and polyester can be suitably used. The metal foil is for preventing permeation of moisture and gas, and foils such as copper, aluminum, and stainless steel can be suitably used. The inner layer polymer film is for protecting the metal foil from the electrolyte stored inside and for melt sealing during heat sealing, and polyolefin or acid-modified polyolefin can be suitably used. The thickness of the laminate film is not particularly limited, and is preferably 1 μm or more and 1 mm or less. For example, in the case of a secondary battery having a rectangular shape in plan view, the exterior body is usually heat-sealed at its periphery in plan view. Specifically, when the exterior body is made of two rectangular exterior body materials, the exterior body is usually heat-sealed at its four sides in plan view, and when the exterior body is made of one rectangular exterior body material, one of the four sides in plan view is usually formed by folding back the exterior body material.

[0087] When the exterior body is a hard case, the hard case is usually formed from a metal plate, and the sealing portion is formed by irradiating the peripheral portion with a laser. The metal plate is generally made of a metal material such as aluminum, nickel, iron, copper, or stainless steel. The thickness of the metal plate is not particularly limited, and is preferably, for example, 1 μm or more and 1 mm or less. The sealing of the metal plates may be achieved by irradiating the overlapping portion of the peripheral portion with a laser.

[0088] The secondary battery 10 of the present invention is effective in increasing the capacity. Since the electrode layer is a semi-solid electrode layer and has fluidity, the thickness of the electrode layer can be stably and easily increased simply by increasing the amount of the electrode layer injected. From this viewpoint, the capacity per electrode area in the secondary battery of the present invention is preferably 4 mAh / cm. 2 More preferably, 5 mAh / cm 2 More than 20mAh / cm 2 In the present invention, since the electrode layer is a semi-solid electrode layer, the capacity per electrode area may be the capacity per current collector area. The capacities per electrode area of ​​the positive electrode and the negative electrode may each be independently within the above range.

[0089] The secondary battery of the present invention may further have a protective layer (not shown) on the outer surface of the exterior body.

[0090] [Secondary battery manufacturing method] The secondary battery 10 of the present invention can be manufactured by a method including the following steps: a preparation step of mixing an electrode active material, a conductive assistant, and an electrolyte to prepare a slurry for electrode layers (i.e., a slurry for a positive electrode layer and a slurry for a negative electrode layer); a coating step of coating a current collector with a slurry for electrode layers to form electrode plates (i.e., positive and negative electrode plates); A welding process for welding the tabs to the electrode plates; a housing step of stacking the electrode plates such that positive and negative electrode plates constituting the electrode plates are alternately arranged with separators disposed therebetween, and housing the stack in an exterior packaging material; A vacuum sealing process in which the exterior body material is sealed and a vacuum is created inside the exterior body; A charge-discharge process in which a solid electrolyte interfacial coating is formed on the surface of the negative electrode active material by an initial charging process to form a secondary battery precursor; and An aging step of aging the secondary battery precursor.

[0091] In the preparation step, specifically, a positive electrode active material, a conductive assistant, an electrolyte, and desired additives are mixed and dispersed to prepare a positive electrode layer slurry, and a negative electrode active material, an electrolyte, and, if desired, a conductive assistant are mixed and dispersed to prepare a negative electrode layer slurry.

[0092] In the coating step, more specifically, the positive electrode layer slurry is coated on a positive electrode current collector to form a positive electrode plate, and the negative electrode layer slurry is coated on a negative electrode current collector to form a negative electrode plate. In forming the positive electrode plate and the negative electrode plate, the electrode layer slurry is coated independently on at least one surface (preferably both surfaces) of the current collector.

[0093] In the welding step, specifically, a positive electrode tab is welded to a positive electrode plate. Also, a negative electrode tab is welded to a negative electrode plate. The materials constituting the positive electrode tab and the negative electrode tab are not particularly limited as long as they are conductive, and may be selected from materials similar to those constituting the current collector. The positive electrode tab is preferably made of aluminum from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics. The negative electrode tab is preferably made of copper from the viewpoint of more sufficient prevention of short circuits and further improvement of rate characteristics and cycle characteristics.

[0094] In the storage step, specifically, the positive and negative electrode plates are stacked such that the positive and negative electrode plates are alternately arranged with a separator disposed therebetween. The stack is then stored in an exterior body material. The method of storage is not particularly limited as long as the exterior bodies are arranged at the top and bottom of the stack in a plan view, and may be achieved, for example, by the following method (i) or (ii): Method (i) sandwiching the laminate between two sheets of exterior material; Method (ii) The laminate is housed in a bag-shaped exterior body having an opening on one side in a plan view, the bag-shaped exterior body having been formed in advance by sealing. In the method (i), instead of the two sheets of exterior body material, one continuous sheet of exterior body material may be folded back.

[0095] In the vacuum sealing step, more specifically, the overlapping portions at the periphery of the exterior body material are sealed, and the inside of the exterior body is evacuated. In the above-mentioned storage step, when method (i) is employed, the inside of the exterior body is evacuated while the periphery of the exterior body material is sealed at the overlapping portions. When method (ii) is employed, the inside of the exterior body is evacuated while the opening of the bag-shaped exterior body is sealed at the overlapping portions. Note that the overlapping portions refer to the overlapping portions of the exterior body materials.

[0096] In the charge / discharge process, specifically, a solid electrolyte interface coating (hereinafter referred to as "SEI coating") is formed on the surface of the negative electrode active material by an initial charging treatment.

[0097] The initial charging process is the first charging process performed for the purpose of forming an SEI film on the surface of the negative electrode active material, and is also called a conditioning process or formation process. The SEI film is formed by the reductive decomposition of additives contained in the electrolyte on the surface of the negative electrode active material during this process, and prevents further decomposition of the additives on the surface of the negative electrode active material during use as a secondary battery. The SEI film is usually made of LiF, Li 2 CO 3 , LiOH, and LiOCOOR (R represents a monovalent organic group, for example, an alkyl group). By forming such an SEI coating more uniformly on the surface of the negative electrode active material, decomposition of the electrolyte components in the secondary battery can be prevented, and the capacity stabilization and life extension of the secondary battery can be achieved.

[0098] In the initial charging process, charging may be performed at least once. Usually, charging and discharging are performed one or more times. One charging and discharging includes one charging and one subsequent discharging. When charging and discharging are performed two or more times, the charging and discharging are repeated the corresponding number of times. The number of charging and discharging performed in this process is usually from one to three.

[0099] The charging method may be a constant current charging method or a constant voltage charging method, or a combination of these. For example, constant voltage charging and constant voltage charging may be repeated during one charging. The charging conditions are not particularly limited as long as the SEI coating is formed. From the viewpoint of further improving the uniformity of the thickness of the SEI coating, it is preferable to perform constant current charging and then constant voltage charging.

[0100] The discharge method may be a constant current discharge method or a constant voltage discharge method, or a combination of these. The discharge conditions are not particularly limited as long as the SEI film is formed. From the viewpoint of further improving the uniformity of the thickness of the SEI film, it is preferable to perform constant current discharge.

[0101] In the initial charging process, the secondary battery is usually maintained at a temperature within the range of 25°C to 100°C, preferably within the range of 35°C to 90°C, and more preferably within the range of 40°C to 85°C.

[0102] In the aging process, more specifically, the SEI film is stabilized by a stabilization treatment, which is a treatment for stabilizing the SEI film by leaving the secondary battery after the initial charging treatment in an open circuit state.

[0103] The temperature of the secondary battery in the stabilization treatment is not particularly limited, and may be maintained within a range of, for example, 15° C. or more and 80° C. or less. From the viewpoint of further stabilizing the SEI coating, the secondary battery is preferably maintained at a temperature within a range of 20° C. or more and 75° C. or less, and more preferably at a temperature within a range of 25° C. or more and 70° C. or less. In detail, the temperature can be maintained within the above range by leaving the secondary battery in a space set at a constant temperature.

[0104] The time for which the material is left in the stabilization treatment is not particularly limited as long as the stabilization of the SEI coating is promoted, and is usually from 10 minutes to 30 days. From the viewpoint of further stabilizing the SEI coating, the time is preferably within the range of from 30 minutes to 14 days, and more preferably within the range of from 1 hour to 7 days.

[0105] The method for manufacturing a secondary battery according to the present invention only includes a mixing step and a coating step as electrode manufacturing steps, and only includes a welding step, a housing step, a vacuum sealing step, a charge / discharge step and an aging step as assembly steps.

[0106] On the other hand, a conventional method for producing a secondary battery including a binder-bonded electrode layer includes, as electrode production steps, a preparation step of preparing an electrode layer-forming coating liquid; a coating step of coating a current collector with the electrode layer-forming coating liquid; a drying step of drying the applied electrode layer-forming coating liquid; a pressing step of compacting the electrode layer; a slitting step of cutting the electrode to a desired width; and a cutting step of cutting the electrode cut to the desired width to a desired shape and size to obtain an electrode plate, and includes, as assembly steps, a welding step of welding a tab to the electrode plate; a housing step of stacking the electrode plates so that the positive and negative electrode plates constituting the electrode plates are arranged alternately with a separator arranged between them, and housing the stack in an exterior body material; a liquid injection step of injecting an electrolyte into the exterior body housing the stack; an impregnation step of impregnating the electrodes with the electrolyte under vacuum; a vacuum sealing step of sealing the exterior body; a charge and discharge step of forming a solid electrolyte interface film on the surface of the negative electrode active material by an initial charging treatment to form a secondary battery precursor; and an aging step of aging the secondary battery precursor. Therefore, in the method for producing a secondary battery according to the present invention, both the electrode production process and the assembly process are greatly simplified, and dramatic reductions in capital investment and manufacturing process costs can be achieved. In the secondary battery of the present invention, the secondary battery production process can be significantly simplified, so that capital investment costs and manufacturing process costs can be significantly reduced. In addition, the secondary battery of the present invention does not contain a binder, so low resistance can be achieved, and therefore the rate characteristics are sufficiently excellent. EXAMPLES

[0107] <Secondary battery manufacturing> (Example 1: Semi-solid electrode type secondary battery) Positive electrode preparation The positive electrode active material was lithium cobalt oxide (LCO) with an average particle size of 15 μm (D5 = 8.0 μm (D5 M)) as a conductive additive with an average particle size of 2.8 μm (D5 = 0.75 μm (D5 A )) carbon black was used as the electrolyte in a 1M solution of LiPF 6 The above was dissolved in a mixed solvent (EC:EMC=25:75vol) and the resulting solution was mixed and dispersed in a weight ratio of 78.5:1.5:20.0 to obtain a positive electrode layer slurry with fluidity. The positive electrode layer slurry was applied to a positive electrode active material capacity of 5.0mAh / cm2 on one side. 2 The solution was applied to one side of an Al foil with a thickness of 15 μm by a doctor blade method to obtain a positive electrode plate having an area of ​​10.0 cm×10.0 cm.

[0108] Negative electrode preparation The negative electrode active material was artificial graphite with an average particle size of 10.2 μm (D5 = 6.2 μm), and the electrolyte was 1M LiPF 6 The mixture was mixed and dispersed in a mixed solvent (EC:EMC = 25:75 vol) at a weight ratio of 60.0:40.0 to obtain a slurry for the negative electrode layer with good fluidity. The slurry for the negative electrode layer was mixed in a manner that the capacity of the negative electrode active material on one side was 5.4 mAh / cm 2 The solution was applied to one side of a 12 μm thick Cu foil measuring 10.2 cm×10.2 cm by a doctor blade method to obtain a negative electrode plate.

[0109] Secondary battery production The tab-welded positive and negative electrode plates were laminated together via a separator (thickness: 20 μm) with a pore size D95 value of 0.45 μm in the intermediate layer region, sandwiched between aluminum laminates, and vacuum sealed. After charging and discharging at 0.2 CA, the battery was charged to SOC 70%, and aged at 55 ° C for 24 hours to complete a secondary battery with a capacity of about 500 mAh. In the semi-solid positive electrode, the binder content was 0% with respect to the total amount of the semi-solid positive electrode layer in the secondary battery completed in this example. In the semi-solid negative electrode, the binder content was 0% with respect to the total amount of the semi-solid negative electrode layer in the secondary battery completed in this example.

[0110] In the secondary battery manufactured in this embodiment, the conductive assistant is contained in the positive electrode but not in the negative electrode, so the negative electrode does not contain conductive particles. Therefore, in this secondary battery, the specific particle size-pore size relationship of the present invention is achieved between the positive electrode and the separator arranged in contact with the positive electrode, but is not achieved between the negative electrode and the separator arranged in contact with the negative electrode.

[0111] (Example 2: Semi-solid electrode type secondary battery) A secondary battery was obtained in the same manner as in Example 1, except that a positive electrode layer slurry obtained by the following method was used to prepare the positive electrode, and a separator (thickness: 20 μm) with an intermediate layer region pore size D95 value of 0.85 μm was used to prepare the secondary battery.

[0112] Lithium cobalt oxide (LCO: positive electrode active material) (D5 = 8.0 μm (D5 M )) surface, the average grain size is 1.1 μm (D5 = 0.15 μm (D5 A )) carbon black particles (conductive assistant) were integrated in a predetermined amount. In detail, lithium cobalt oxide (LCO: positive electrode active material), carbon black particles (conductive assistant) and polyvinylidene fluoride (PVdF: molecular weight 300,000) were each charged in a predetermined amount into a mechanical mixer (manufactured by Hosokawa Micron Corporation, Nobilta), and mixed for 30 minutes to integrate the carbon black particles on the surface of lithium cobalt oxide. The predetermined amount of the positive electrode active material and conductive assistant is an amount such that the ratio of the positive electrode active material and conductive assistant of the positive electrode in the secondary battery completed in this embodiment is the same as the ratio of the positive electrode active material and conductive assistant of the positive electrode in the secondary battery completed in Example 1. The predetermined amount of PVdF is 0.13 parts by mass per 100 parts by mass of lithium cobalt oxide. The content of the binder containing PVdF was 0.1 mass% or less with respect to the total amount of the semi-solid positive electrode layer in the secondary battery completed in this embodiment. A positive electrode layer slurry was obtained by the same method as the method for producing the positive electrode layer slurry in Example 1, except for using the obtained integrated material of the positive electrode active material and the conductive additive particles. In detail, the obtained integrated material of the positive electrode active material and the conductive additive particles and 1M LiPF 6 The above was dissolved in a mixed solvent (EC:EMC=25:75 vol) and the solution was mixed and dispersed so that the weight ratio of active material:conductive additive:binder:solvent was 78.4:1.5:0.1:20.0, to obtain a positive electrode layer slurry with good fluidity. In the semi-solid negative electrode, the content of the binder was 0.1 mass % or less with respect to the total amount of the semi-solid negative electrode layer in the secondary battery completed in this example.

[0113] In the secondary battery manufactured in this embodiment, the conductive assistant is integrated with the surface of the positive electrode active material and is contained in the positive electrode, but is not contained in the negative electrode, so the negative electrode does not contain conductive particles. Therefore, in this secondary battery, the specific particle size-pore size relationship of the present invention is achieved between the positive electrode and the separator arranged in contact with the positive electrode, but is not achieved between the negative electrode and the separator arranged in contact with the negative electrode.

[0114] (Comparative Example 1: Binder-bonded electrode type secondary battery) Positive electrode preparation The positive electrode active material was lithium cobalt oxide (LCO) with an average particle size of 15 μm (D5 = 8.0 μm (D5 M )) was dispersed in NMP with carbon black having an average particle size of 1 μm as a conductive additive and PVdF as a binder in a weight ratio of 96:2:2 to obtain a positive electrode slurry. 2 The mixture was applied to one side of an Al foil with a thickness of 15 μm and dried, after which it was compressed using a roll press machine to a porosity of 18%, and then slit and cut to obtain a positive electrode plate of 10.0 cm × 10.0 cm.

[0115] Negative electrode preparation The negative electrode slurry was obtained by dispersing artificial graphite with an average particle size of 10 μm as the negative electrode active material, flake graphite with an average particle size of 3 μm as the conductive assistant, and CMC and SBR as the binder in a weight ratio of 96:1:3 (1.5 + 1.5) in water. Then, the active material capacity on one side was 5.4 mAh / cm using a die coater. 2 After coating and drying on one side of a 12 μm thick Cu foil so that the porosity was 23%, the foil was compressed using a roll press machine, and then slit and cut to obtain a negative electrode plate of 10.2 cm × 10.2 cm.

[0116] Secondary battery production The tab-welded positive and negative electrodes were laminated together with a separator having a pore size D95 of 0.85 μm in the intermediate layer region (similar to the separator used in Example 2), sandwiched between aluminum laminates, and filled with an electrolyte (LiPF at 1M). 6 A solution of these in a mixed solvent (EC:EMC=25:75vol) was poured into the battery, which was then vacuum-impregnated and vacuum-sealed. After charging and discharging at 0.2CA, the battery was charged to SOC70% and aged at 55℃ for 24 hours to complete a secondary battery with a capacity of approximately 500mAh. In the semi-solid negative electrode, the content of the binder was 0.01 mass % or less with respect to the total amount of the semi-solid negative electrode layer in the completed secondary battery in this example.

[0117] (Comparative example 2: Semi-solid electrode type secondary battery) A secondary battery was obtained in the same manner as in Example 1, except that a positive electrode layer slurry obtained by the following method was used to prepare the positive electrode, and a separator having an intermediate layer region pore size D95 value of 0.85 μm (a separator similar to the separator used in Example 2) was used to prepare the secondary battery. The positive electrode active material was lithium cobalt oxide (LCO) with an average particle size of 15 μm (D5 = 8.0 μm (D5 M )) as a conductive additive with an average particle size of 1.1 μm (D5 = 0.15 μm (D5 A )) carbon black was used as the electrolyte in a 1M solution of LiPF 6The above was dissolved in a mixed solvent (EC:EMC=25:75 vol) and the resulting solution was mixed and dispersed in a weight ratio of 78.5:1.5:20.0 to obtain a positive electrode layer slurry with fluidity.

[0118] <Evaluation and Measurement> (Minimum particle size D5 value) The sample was dispersed in NMP while applying ultrasonic waves, and the particle size distribution was measured using a laser diffraction / scattering type particle size distribution measuring device (LA-960 manufactured by Horiba, Ltd.), and the D5 value was obtained from the results. For example, using an active material as a sample, the minimum particle diameter D5 M obtained. For example, a conductive additive is used as a sample, and the minimum particle diameter D5 A obtained. In addition, for example, a sample is prepared by integrating a positive electrode active material and conductive additive particles, and the minimum particle diameter D5 P obtained.

[0119] (Separator maximum pore size D95 value) The cross section of the separator was exposed by FIB processing (Focused Ion Beam) while cooling, and a cross section image was obtained by SEM observation. In the cross section image, the pore size distribution of the intermediate layer region excluding 15% of the region at both ends (i.e., top and bottom) was measured using image analysis software (ImageJ (Wayne Rasband (NIH))), and the D95 value was obtained from the result.

[0120] (Short rate) The completed secondary batteries were checked for the presence or absence of electrical short circuits, and the short circuit rate was calculated. When the separator is impregnated with the electrolyte contained in the electrode during cell production, if the electrolyte contains conductive additive particles smaller than the pore size of the separator, an initial short circuit may occur, although the probability is low, so this is expressed as the short circuit rate.

[0121] (Rate characteristics) The completed secondary batteries were each measured for capacity retention rate X (0.2 CA discharge capacity ratio) when discharged at 2 CA at 25°C. ◎◎; 85% < X (best); ◎; 80% < X ≤ 85% (excellent); ○; 70% < X ≤ 80% (good); △; 50% < X ≤ 70% (no practical problem); ×; X ≤ 50% (there is a practical problem).

[0122] (Cycle characteristics) Using the completed various secondary batteries, the 0.2CA capacity retention rate Y was measured when full charge and discharge (3.00V to 4.35V) at a current of 0.5CA was repeated 300 cycles at 35°C. Specifically, the 0.2CA capacity retention rate Y is the ratio of the 0.2CA discharge capacity at the 300th cycle to the 0.2CA discharge capacity at the first cycle. ◎◎; 85% < Y (best); ◎; 80% < Y ≤ 85% (excellent); ○; 70% < Y ≤ 80% (good); △; 50% < Y ≤ 70% (no practical problem); ×; Y ≤ 50% (there is a practical problem).

[0123] The various evaluation levels and evaluation results are shown in Table 1.

[0124]

Table 1

[0125] The symbols in Table 1 are as follows. (1) It is the D5 value of the active material used. (2) It is the D5 value of the conductive additive used. (3) It is the D5 value of the conductive particles in the electrode layer. ※1: Mixing, coating, drying, pressing, slitting (cutting) (Slitting is a process with the same meaning as cutting) ※2: Tab welding, laminate sandwiching, liquid injection, vacuum impregnation, vacuum sealing, charge and discharge, aging ※3: Mixing, coating ※4: Tab welding, laminate sandwiching, vacuum sealing, charge and discharge, aging

[0126] 5.0 mAh / cm in all examples and comparative examples 2 The secondary battery is produced in a region where the weight per unit area is very large. For this reason, the resistance is high and the rate characteristic and cycle characteristic are poor in Comparative Example 1 produced by a normal method including a binder.

[0127] In Comparative Example 2, which uses a binder-free, fluid electrode, the secondary battery manufacturing process can be significantly simplified and the 2CA capacity retention rate can be improved, but the minimum particle size of the conductive particles and the maximum pore size of the separator do not satisfy the required relationship, resulting in a high short-circuit rate and poor cycle characteristics.

[0128] In Example 1, in which the conductive assistant and the separator were changed so that the minimum particle size of the conductive particles and the maximum pore size of the separator satisfied a predetermined relationship, the short circuit rate, rate characteristics, and cycle characteristics were sufficiently excellent.

[0129] In addition, in Example 2, by using conductive particles that are attached and integrated onto the surface of the active material, even if conductive particles smaller than the maximum pore size of the separator are used, the relationship between the minimum particle size and the maximum pore size can be satisfied, and therefore the same effects as in Example 1 can be obtained. [Industrial Applicability]

[0130] The secondary battery of the present invention can be used in various fields where battery use or storage is anticipated. By way of example only, the secondary battery of the present invention can be used in electronics packaging fields. The secondary battery according to an embodiment of the present invention can also be used in the electrical, information, and communication fields in which mobile devices and the like are used (e.g., electrical and electronic devices fields including small electronic devices such as mobile phones, smartphones, smart watches, notebook computers, digital cameras, activity meters, arm computers, electronic paper, wearable devices, RFID tags, and card-type electronic money, or mobile device fields), household and small industrial applications (e.g., power tools, golf carts, household, nursing care, and industrial robots), large industrial applications (e.g., forklifts, elevators, and port cranes), transportation systems (e.g., hybrid cars, electric cars, buses, trains, electrically assisted bicycles, and electric motorcycles), power system applications (e.g., various power generation, road conditioners, smart grids, and general household installation-type power storage systems), medical applications (medical devices such as earphones and hearing aids), pharmaceutical applications (medical management systems), IoT, and space and deep sea applications (e.g., space probes, submersible research vessels, and the like).

Claims

1. A semi-solid electrode including an electrode active material, a conductive assistant, and an electrolyte, and a separator disposed in contact with the semi-solid electrode, The minimum particle size D5 of the conductive particles contained in the semi-solid electrode P (μm) is greater than the maximum pore diameter D95 (μm) of the intermediate layer region of the separator, The conductive particles are the conductive assistant, integrated particles in which the conductive assistant is integrated with the surface of the electrode active material, or a mixture thereof.

2. 2 . The secondary battery according to claim 1 , wherein the intermediate layer region is a region excluding 15% of the thickness of the separator at each end in the thickness direction in a cross section parallel to the thickness direction of the separator.

3. the semi-solid electrode comprises a semi-solid positive electrode and a semi-solid negative electrode; The minimum particle size D5 P 2. The secondary battery according to claim 1, wherein the relationship between the maximum pore diameter D95 (μm) and the maximum pore diameter D95 (μm) is achieved between at least one of the semi-solid positive electrode and the semi-solid negative electrode and the separator arranged in contact with the electrode.

4. The conductive assistant has a minimum particle size D5 that is equal to or smaller than the maximum pore size D95 (μm) of the intermediate layer region of the separator. A (μm), The secondary battery according to claim 1 , wherein the conductive assistant constitutes integrated particles in which the conductive assistant is integrated with a surface of the electrode active material.

5. The minimum particle size D5 of the conductive particles P 2. The secondary battery of claim 1, wherein the maximum pore diameter D95 (μm) of the intermediate layer region of the separator satisfies the following relationship: 0.1≦D5 P -D95≦10。

6. The minimum particle size D5 of the conductive particles P The secondary battery according to claim 1 , wherein the thickness is 0.3 μm or more and 15 μm or less.

7. The minimum particle size D5 of the conductive particles P 2. The secondary battery of claim 1, wherein the maximum pore diameter D95 (μm) of the intermediate layer region of the separator satisfies the following relationship: 1≦D5 P -D95≦9。

8. The minimum particle size D5 of the conductive particles P The secondary battery according to claim 7 , wherein the thickness is 1 μm or more and 10 μm or less.

9. 2. The secondary battery according to claim 1, wherein the maximum pore diameter D95 of the intermediate layer region of the separator is 0.2 μm or more and 5 μm or less.

10. The capacity per area of ​​the semi-solid electrode is 4 mAh / cm 2 The secondary battery according to claim 1 .

11. The secondary battery according to claim 1 , wherein the content of the binder in the semi-solid electrode is 0.1 mass % or less with respect to the total amount of the semi-solid electrode layer.

12. The secondary battery according to claim 1 , wherein the semi-solid electrode has an electrode layer capable of absorbing and releasing lithium ions.

13. A method for producing the secondary battery according to any one of claims 1 to 12, comprising the following steps: a preparation step of mixing an electrode active material, a conductive assistant, and an electrolyte solution to prepare a slurry for an electrode layer; A coating step of coating a current collector with a slurry for an electrode layer to form an electrode plate; a welding step of welding the tab to the electrode plate; a housing step of stacking the electrode plates such that the positive and negative electrode plates are alternately arranged with separators disposed therebetween, and housing the stack in an exterior packaging material; a vacuum sealing step of sealing the exterior body material and creating a vacuum inside the exterior body; A charge-discharge process in which a solid electrolyte interfacial coating is formed on the surface of the negative electrode active material by an initial charging process to form a secondary battery precursor; and An aging step of aging the secondary battery precursor.

Citation Information

Patent Citations

  • Separator for electrochemical element, electrochemical element, and method of manufacturing the same

    JP2011228188A

  • Semi-solid electrodes with high speed capability

    JP2016500465A

  • Lithium ion secondary battery separator and lithium ion secondary battery

    JP2019175703A

  • Method for manufacturing non-aqueous electrolyte secondary battery

    JP2019186009A

  • Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery using the same

    JP2020061332A